Akseptabilitas Poligami di Kalangan Para Janda di Desa Pangarungan Kecamatan Torgamba Kabupaten Labuhanbatu Selatan Provinsi Sumatera Utara Indonesia - Syafrizal Nasution; Irwan (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
This research aims to reveal the acceptance of polygamy among widows in Pangurungan Village, North Sumatra. This research problem can be formulated as follows: What is the acceptability of polygamy among widows in Pangarungan village, and what factors influence the readiness for polygamy for widows in Pangarungan village. The research method used is a qualitative research method with a phenomenological approach. The research subjects were a sample of 10 widows who had income from a total population of 63 widows. Data was obtained through interviews, observation and document study. The results of the research show that 50% of widows in the Pengarungan Village community, North Sumatra have a tendency to agree with the practice and implementation of polygamy. Apart from conceptually, they agree and some are even ready to undergo polygamy. Meanwhile, the other 50% do not agree with the concept of polygamy and are not willing to be polygamous.